PERAN GURU DALAM MENGEMBANGKAN LITERASI MEMBACA SISWA DI SEKOLAH DASAR DI KELURAHAN SUNYARAGI - Muallipah; Renata Elsinta; Suherli Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy plays a crucial role in supporting cognitive growth and student learning success at the elementary school level. However, students' interest in reading and their literacy habits still face several challenges. This study aims to explain the role of teachers in improving students' reading literacy in Sunyaragi Village. This study used a qualitative approach with descriptive methods. Data were collected through semi-structured interviews and documentation with six elementary school teachers selected using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research findings indicate that teachers play a strategic role as facilitators, motivators, guides, evaluators, and drivers of a culture of literacy through classroom learning activities, reading habit programs, and the use of learning media. In general, students' reading ability is in the fairly good category, although several obstacles remain, such as low interest in reading, high use of gadgets, lack of reading habits at home, and difficulty in understanding reading content. Teachers address these issues through extra mentoring, literacy enrichment activities, and ongoing evaluation of reading development. This research indicates that developing effective reading literacy requires collaboration between teachers, schools, and parents to build a sustainable literacy culture in elementary education.